A NEW SPECIES OF TRIBELOCEPHALA (HETEROPTERA : REDUVIIDAE) FROM WESTERN GHATS - LIVINGSTONE, DAVID; RAVICHANDRAN, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
A new species of the genus Tribelocephala Stal namely Tribelocephala uppasi from Western uhaus has been described and illustrated.